2019
DOI: 10.3389/fcimb.2019.00350
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Tandem Mass Tag-Based Quantitative Proteomic Analysis of Tachaea chinensis Isopod During Parasitism

Abstract: Parasitic isopods perforate and attach to the host integument via the mandibles and then feed on hemolymph and exudate from the wounds. Such isopods attack a variety of commercially important fish and crustacean hosts. Similar to other hematophagous parasites, isopods may also employ biomolecules that affect host blood conglutination and defense systems. In the present study, a tandem mass tag-based quantitative proteomic approach was used to identify differentially expressed proteins in Tachaea chinensis para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The salinity tolerance of other isopod species, such as Sphaeroma serratum , which usually inhabit coastal marine or brackish waters, has been studied, and the results showed that S. serratum is euryhaline, with lower and upper limits of ~2‰ and 74‰, respectively 25 . Tachaea chinensis not only has a strong salinity tolerance in different regions, but also survives in freshwater environments such as rivers and rice fields 26,27 . Although the salinity adaptation mechanisms of T. chinensis are unclear, these abilities are important for the adaptation of the species to different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The salinity tolerance of other isopod species, such as Sphaeroma serratum , which usually inhabit coastal marine or brackish waters, has been studied, and the results showed that S. serratum is euryhaline, with lower and upper limits of ~2‰ and 74‰, respectively 25 . Tachaea chinensis not only has a strong salinity tolerance in different regions, but also survives in freshwater environments such as rivers and rice fields 26,27 . Although the salinity adaptation mechanisms of T. chinensis are unclear, these abilities are important for the adaptation of the species to different environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, 1166 differentially expressed proteins were identified, with 641 up- and 525 downregulated proteins in adults versus plerocercoids, which was similar to our previous RNA-seq study, except that we identified slightly more upregulated genes in adults [ 11 ], indicating the accuracy of the quantitative proteomic results. Nevertheless, 860 hypothetical proteins and 306 described proteins were identified among these DEPs, possibly because limited reference omics data were available and few studies have been conducted on this species [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The manca stage passes through five distinct embryonic stages within 30–38 days, although the period from the manca stage to the mature adult stage may span 180 days on average ( Xu et al, 2021 ). Tachaea chinensis is commonly found adhering to the carapace of shrimps, which can cause various physiological effects and potential secondary infections ( Nagasawa et al, 2018 ; Li et al, 2019a , 2019b , 2020 ; Ueki et al, 1988 ).…”
Section: Introductionmentioning
confidence: 99%